Assessment of the Impact of Government Revenue Mobilisation on Economic Growth in Nigeria - Comfort Omolayo Rotimi; Naphtali John; Mathew Ekundayo Rotimi; Mishelle Doorasamy (Journal of Economics, Business, and Accountancy Ventura, 2021)
Inadequate revenue generation impedes economic growth. The issue has lacked attention from academics. Therefore, this study focuses on the relationship between revenue generation and economic growth in Nigeria. It employed time series data sourced from the Central Bank of Nigeria (CBN) and the National Bureau of Statistics (NBS) from 1981-2018. The study used multiple regression to estimate the impact of government revenue mobilization on economic growth in Nigeria. Findings revealed that domestic debts and non-oil revenue positively and significantly impact economic growth, while external debts and oil revenue were otherwise. The study concluded that government revenue impacts economic growth. Consequently, the study recommends economic diversification through strategic programs to enhance growth rather than remaining a mono-economy. Furthermore, it recommends that the government review the existing revenue mobilization strategy– especially the diverse non-oil revenue bases to ensure improved revenue remittances. The study also recommended formulating policies that will guarantee better utilization of domestic and foreign loans to increase productivity and enhance revenue mobilization. It is also recommended that borrowing be considered a last resort to fund government projects, and where it is unavoidable, such borrowing should be limited to domestic debt.